Attitudes towards urban green during the COVID-19 pandemic via Twitter. (July 2022) - Marchi, V.; Speak, A.; Ugolini, F.; Sanesi, G.; Carrus, G.; Salbitano, F.
Abstract: COVID-19 has had economic, social and environmental impacts worldwide. Governments have adopted containment measures to limit the spread of the virus. Urban green spaces (UGSs) were included among the non-essential activities and were consequently closed during the lockdown periods in some countries. This study analysed tweets posted by users to understand the citizens' perception and sentiment in relation to the closure of UGS in Italy. Results revealed that people felt a strong deprivation feeling in relation to the restrictions imposed on UGS access, which limited the number of spaces for supporting mental and physical wellbeing of citizens. Users from urban areas were more affected by the lockdowns and more willing to share thoughts on social media, demonstrating a strong emotionality. Furthermore, findings show that users seemed concerned about their children's health, expressing awareness about the benefits of being in contact with nature. UGS is able to provide services to citizens, and close-to-home parks are fundamental for the community, in particular during a health emergency. The implementation of urban design, which includes green areas to support health and environment challenges, should be addressed by policy-makers to create opportunities for a green and resilient recovery of cities, and prepare for future emergencies. Highlights: The closure of urban green spaces produced a strong deprivation feeling in citizens. Urban green spaces provide services and relief to citizens during a health emergency. Twitter users expressed concern for the health of their children, stressing benefits of contact with nature. Planning green spaces is fundamental for the recovery of cities and preventing future emergencies.